Christian mysticism an introduction to contemporary theoretical approaches - Nelstrop, Louise; Magill, Kevin J., 1972-; Onishi, Bradley B. (Farnham, Surrey, England ; Burlington, VT : Ashgate, 2009)
This book introduces students to Christian mysticism and modern critical responses to it. Christianity has a rich tradition of mystical theology that first emerged in the writings of the early church fathers, and flourished during the Middle Ages. Today Christian mysticism is increasingly recognised as an important Christian heritage relevant to today's spiritual seekers.The book sets out to provide students and other interested readers with access to the main theoretical approaches to Christian mysticism - including those propounded by William James, Steven Katz, Bernard McGinn, Michael Sells
Introduction: Contemporary theoretical approaches -- Key themes and motifs -- Platonism and Christian mysticism -- Negative or apophatic language -- Selfhood and interiority -- Erotic imagery -- Hierarchy -- Symbolism and Scripture : mystical sense -- Later developments in Christian mysticism -- Female mysticism -- Visionary mysticism -- Imaginative mysticism, meditation, and experience -- Mysticism and heresy -- Postmodern re-readings of pseudo-Denys and Augustine -- Exploring negative language through pseudo-Denys : Derrida and Marion -- Exploring negative language through Augustine : Marion, Derrida and Lyotard -- Conclusion: What is Christian mysticism?
Includes bibliographical references and index.
Description based on print version record.
Keywords: Mysticism; Philosophy and religion; RELIGION / Mysticism; Electronic books